Adopting international recommendations to design a model for maternal health service to cope with pandemic disruption for Indonesian primary care - Fitriana Murriya Ekawati; Mumtihana Muchlis; Amita Tuteja (BMC, 2023)
Plain language summary Much evidence on maternal care is available, however, little is known about their potential adoption for improving maternal health services in Indonesian primary care during the COVID-19 pandemic. This study reports the adoption of international recommendations to develop a model for improving maternal health services in primary care to cope with disruptions caused by the COVID-19 pandemic, including potential barriers of recommendation uptake in practice. Further research is desired to pilot the recommendation in practice.